Measurement and theory of core inflation - Martin Almuzara; Argia M. Sbordone (Federal Reserve Bank of New York, 2024)
We discuss the concept of core inflation and its relevance for policymakers and then review a variety of approaches that have been pursued for the construction of informative core measures. After illustrating some empirical patterns displayed by U.S. inflation data and discussing conceptual issues around measurement, we provide a unified framework to interpret various widely used core measures and compare their relative properties.
Keywords: E31; E32; E52; 330; inflation; core inflation